A game of ghosts - Connolly, John, 1968- (New York : Emily Bestler Books/Atria, 2017)
The latest thriller in the Charlie Parker detective series, in which a private detective has vanished and Parker is hired to track him down.
Keywords: Parker, Charlie "Bird" (Fictitious character) -- Fiction; Private investigators -- Fiction; Thrillers (Fiction); Detective and mystery fiction